A influência da cultura organizacional na adoção dos controles gerenciais em restaurantes japoneses de Campo Grande/MS - Caio Saab Orsini (2023)
Managerial controls highly affect the companies’ survival, especially SMEs, as they will help the company adapt to the environment and achieve the desired outcomes. The organizational culture was approached in this research as a determining factor for the establishment of managerial controls. The objective of this study is to analyze how organizational culture influences the adoption of managerial controls in Japanese restaurants in Campo Grande/MS. Toward this, a qualitative research of multiple case studies was conducted, where two Japanese restaurants in the city of Campo Grande/MS were analyzed, one located in the Central Market and the other in the central region of the city. Data was collected through the author’s direct observation, visits to the participating restaurants' social networks and conducting semi-structured interviews with the founders/managers of the restaurants. For data processing, the software Iramuteq was used, and data analysis was based on the content analysis technique proposed by Bardin (1977). The results of the analyzes showed strong differences in the organizational culture of the restaurants, in addition to revealing that the revealed culture directly influences the adoption of managerial controls in the participating restaurants, with these controls revealed to be mostly informal. It was found that the organizational culture caused significant structural changes and different ways of adapting in face of the incoming challenges, leading each restaurant to adopt organizational structures that were very different from each other, with very different organizational identities. In restaurant A, the environment is more inclusive, the communication process is effective, vision and values are coherent with organizational objectives, the manager adopts a more aggressive stance focused on market innovation, encourages teamwork, focuses on customer satisfaction client and provides training and onboarding. In restaurant B, there was a greater power distance, a disorganized environment, the work process is individualistic, organizational communication is inadequate, the manager focuses only on the quality of the product, vision and values do not match the organizational objectives and with the manager's attitude. The evolutionary level of perceived management controls is initial, almost rudimentary in one of the analyzed restaurants. As a practical contribution, based on the results, it is suggested that the restaurants integrate new management controls that allow a more detailed analysis of the incoming and outcoming costs, so that a future study to cost reduction is possible. Specifically for the restaurant at the Central Market, another suggestion would be to review its mission and vision in order to better reflect the beliefs and values exposed, in addition to clearly sharing it with all employees. As an academic contribution, this research brings a new perspective by treating organizational culture as a strategic element for the adoption of formal and informal management controls and differentiates itself by addressing a direct relationship between organizational culture and the adoption of management controls, explaining the choice of types of controls used in the organizations studied to achieve their strategic objectives. It is expected that this study contributes to the state of the art regarding the relationship between organizational culture and management controls. As a recommendation for future research, it is suggested to analyze the level of impact of the environment in which the company is inserted in the formation of the organizational culture and in the adoption of management controls.